Dialectical behavior therapy skills training affects defense mechanisms in borderline personality disorder: An integrative approach of mechanisms in psychotherapy. (8th November 2019) - Euler, Sebastian; Stalujanis, Esther; Allenbach, Gilles; Kolly, Stéphane; de Roten, Yves; Despland, Jean-Nicolas; Kramer, Ueli
Abstract: Objective: Borderline personality disorder (BPD) is characterized by immature defense mechanisms. Dialectical behavior therapy (DBT) is an effective treatment for BPD. However, understanding the underlying mechanisms of change is still limited. Using a transtheoretical framework, we investigated the effect of DBT skills training on defense mechanisms. Method: In this randomized controlled trial, 16 of 31 BPD outpatients received DBT skills training adjunctive to individual treatment as usual (TAU), while the remaining 15 received only individual TAU. Pre–post changes of defense mechanisms, assessed with the Defense Mechanism Rating Scale, were compared between treatment conditions using ANCOVAs. Partial correlations and linear regressions were conducted to explore associations between defenses and symptom outcome. Results: Overall defense function improved significantly more in the skills training condition ( F (1, 28) = 4.57, p = .041). Borderline defenses decreased throughout skills training, but not throughout TAU only ( F (1, 28) = 5.09, p = .032). In the skills training condition, an increase in narcissistic defenses was associated with higher symptom scores at discharge ( β = 0.58, p = .02). Conclusions: Although DBT does not explicitly target defense mechanisms, skills training may have favorable effects on defense function in BPD. Our findings contribute to an integrative understanding of mechanisms of change in BPD psychotherapy.